Totally ecofriendly synthesis of silver nanoparticles from aqueous dissolutions of polysaccharides - Garza Navarro, Marco Antonio; Aguirre Rosales, José Augusto; Llanas Vázquez, Erika Elizabeth; Moreno Cortez, Iván Eleazar; Torres Castro, Alejandro; González González, Virgilio Ángel (2013)
In this contribution, a totally ecofriendly synthesis of silver nanoparticles from aqueous dissolution of polysaccharides is reported. The synthesis of nanoparticles was performed using aqueous dissolutions of silver nitrate (AgNO3) and carboxymethyl-cellulose (CMC) as both reducing and stabilization agent and using different AgNO3 : CMC weight ratios. Resultant yellowish to reddish dispersions were characterized by means of transmission electron microscopy and their related techniques, such as bright field and Z-contrast imaging and electron diffraction, as well as ultraviolet-visible and infrared spectroscopic techniques. The experimental evidence suggests that the morphology and particle size distribution of the silver nanoparticles depend on the AgNO3 : CMC weight ratio. This feature seems to be related to the stabilization given by the CMC matrix, which, according to our experimental findings, is steric in nature. Regarding such experimental evidence, a synthesis mechanism in which CMC acts as stabilizer and reducing agent is proposed.